Understanding the use of geographical information systems (GIS) in health informatics research: A review - Shaw, Nicola; McGuire, Suzanne (BMJ health & care informatics, 2017)
Background: The purpose of this literature review is to understand geographical information systems (GIS) and how they can be applied to public health informatics, medical informatics, and epidemiology.Method: Relevant papers that reflected the use of geographical information systems (GIS) in health research were identified from four academic databases: Academic Search Complete, BioMed Central, PubMed Central, and Scholars Portal, as well as Google Scholar. The search strategy used was to identify articles with “geographic information systems”, “GIS”, “public health”, “medical informatics”, “epidemiology”, and “health geography” as main subject headings or text words in titles and abstracts. Papers published between 1997 and 2014 were considered and a total of 39 articles were included to inform the authors on the use of GIS technologies in health informatics research.Results: The main applications of GIS in health informatics and epidemiology include disease surveillance, health risk analysis, health access and planning, and community health profiling. GIS technologies can significantly improve quality and efficiency in health research as substantial connections can be made between a population’s health and their geographical location.Conclusions: Gains in health informatics can be made when GIS are applied through research, however, improvements need to occur in the quantity and quality of data input for these systems to ensure better geographical health maps are used so that proper conclusions between public health and environmental factors may be made.